Determination of antimicrobial activity and some biochemical properties of honey and propolis in Turkish markets - Gur, Nazmi; Bayrak, Neval; Topdemir, Aykut (Mattioli 1885, 2020)
We examined the antibacterial activity, microflora, fatty acid composition and protein content of five honey and five propolis samples from Turkish markets. The in vitro antimicrobial activity of the samples was analysed using 10 bacteria (Streptococcus sp., Pseudomonas aeruginosa DSM 50071, Escherichia coli ATCC 25922, Salmonella typhimurium NRRL 4463, Staphylococcus aureus ATCC 6538 P, Bacillus subtilis ATCC 6033, Enterobacter aerogenes CCM 2531, B. subtilis niger, Klebsiella pneumoniae FMC 5, 102Proteus vulgaris FMC 11) and two yeasts (Candida glabrata ATTC 66032, Saccharomyces cerevisiae UGA). The honey samples exhibited antimicrobial activity against six bacteria and one yeast, whereas the propolis samples exhibited antimicrobial activity against all microorganisms tested. Propolis samples contained 7-16 different fatty acids, whereas three of the five honey samples contained no fatty acids, and the protein content of propolis was higher than that of honey. Thus, both propolis and honey exhibited antimicrobial activity, the former being more effective.
Keywords: antimicrobial; honey; propolis